Introducing the Value of Nationalism through Children’s Literacy: Optimizing the Digital Platform - Adelia Savitri; Zuhda Mila Fitriana; Eka Nanda Ravizki; Rafi Great Akbar; Syaifulloh Umar (Future Science, 2022)
Nationalism, national defense education, and eco-awareness are relatable. While nationalism is considered a value instilled in one’s heart, national defense is defined as an attitude of realizing nationalism through activities that share the same objectives - protecting, defending, and growing the nation. One good way to instill the character of nationalism is by utilizing literature, specifically creative children’s literacy, through the digital platform which is inclusively accessible nowadays. It is expected to spread the awareness of nationalism values in children. This study observed the knowledge obtained by children in Taman Baca Masyarakat (Public Library) RW 02 Pradah Kali Kendal, represented in a story writing activity. The value of state defense introduced is limited to three aspects – anticorruption, eco-awareness, and culture-awareness. This study finds that children in Public Library RW 02 Pradah Kali Kendal obtained knowledge about nationalism values and awareness well. The children are also willing to apply a digital platform to spread their values and understanding through children’s literacy. It represents the creative literacy writings written by the children in Public Library RW 02 Pradah Kali Kendal.